KEPUASAN KERJA MEMEDIASI PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASIONAL KUTABEX BEACH FRONT HOTEL BALI - Yulianingsih, Ni Luh Sintya; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen; Vol 9 No 5 (2020), 2020)
Organizational commitment is an attitude that shows employee loyalty and ongoing process of how they expresses their attention to organization's success. Purpose of study is to analyze the role of job satisfaction in mediating effect of transformational leadership on organizational commitment of KutaBex Beach Front Hotel Bali employees. The population was 113 people and the sample are 54 people using proportionate random sampling method. Data are analyzed using path analysis techniques. Data collection through interviews and questionnaires. The results showed that transformational leadership had a positive and significant effect on job satisfaction and organizational commitment. In addition, job satisfaction has a positive and significant effect on organizational commitment and job satisfaction mediates the effect of transformational leadership on organizational commitment partially. The implication of this research is that high job satisfaction owned by employees will increase employee organizational commitment through the influence of transformational leadership. Keywords: transformational leadership, job satisfaction, organizational commitment